Synthesis and structural characterization of nano-sized nickel ferrite obtained by mechanochemical process - Hajalilou, Abdollah; Hashim, Mansor; Kahrizsangi, Reza Ebrahimi; Mohamed Kamari, Halimah; Sarami, Nahid (Elsevier, 2014)
NiFe2O4 nanoparticles were synthesized by a mechanochemical reaction of NiO and Fe2O3 powders in a high energy planetary ball milling machine. The XRD characterization results suggested that in the case of nano ferrite, milling up to 18 h formed NiFe2O4 particles of 10 nm with some residual Fe2O3 particles through a solid state reaction. By extending milling time to 30 h, the amorphous phase of NiFe2O4 was produced due to the high energy released during mechanical activation. The mechanism was identified as one of diffusion and counter-diffusion of Ni+2 and Fe+3 ions of the starting materials into each other. FT-IR analysis showed two absorption bands in the nickel ferrite structure related to octahedral and tetrahedral sites, respectively, in the range of 400–600 cm−1. The vibrating sample magnetometric (VSM) studies showed that the nano-sized particles of nickel ferrite exhibited a ferromagnetic behavior and its coercivity was approximately negligible.